Piloting staff education in Australia to reduce falls in older hospital patients experiencing delirium - Toye, Christine; Kitchen, S.; Hill, A.; Edwards, D.; Sin, M.; Maher, Sean (Wiley-Blackwell Publishing Asia, 2016)
This study piloted a hospital-based delirium and falls education program to investigate the impacts on staff knowledge and practice plus patient falls. On a medical ward, staff knowledge was compared before and after education sessions. Other data – collected a day before and after program implementation – addressed documentation of patients' delirium and evidence of compliance with falls risk minimization protocols. These data, and numbers of patient falls, were compared before and after program implementation. Almost all ward staff members participated in education sessions (7 doctors, 7 allied health practitioners, and 45 nurses) and knowledge was significantly improved in the 22 who completed surveys both before and after session attendance. Patients assessed as having delirium (5 before implementation, 4 afterwards) were all documented as either confused or delirious. Small changes eventuated in adherence with falls risk management protocols for confused patients and the number of falls decreased. The program merits a stronger emphasis on staff activities relating to the detection, documentation, and management of delirium to inter-professional roles and communication. Evidence of practice enhancement from program implementation should precede rigorous testing of impacts upon falls.